Humidity Sensors Types and Applications - Tariq Saeed Chani, Muhammad; Mohammed Asiri, Abdullah; Bahadar Khan, Sher (IntechOpen, 2023)
Humidity is the presence of water vapor in the air. In view of its effect on human health and the physical qualities of materials, humidity must be measured and controlled. Humidity measurement is imperative in a variety of fields including health care, environmental monitoring, automobiles, air-conditioning, civil engineering, agriculture, semiconductors, pharmaceuticals, textiles, paper and processing industries. This book provides an overview of humidity and the types and applications of humidity sensors. This book will be helpful for students, researchers and general readers.